Integration of sport and education in China: a case study of a dual career development environment of a Shanghai junior men`s basketball team - Jiang, X.; Wang, K. (International Journal of Sport and Exercise Psychology, 2025)
In the context of China`s integration of sports and education (ISE), a Shanghai junior men`s basketball team was established through a collaboration between a district elite sport school and six regular schools. Using the holistic ecological approach, this case study investigated the dual career development environment (DCDE) of the team, aiming to (a) describe the successful DCDE and (b) identify factors influencing its effectiveness (DC-ESF). Data were collected from key stakeholders via participant observations, informal talks, and formal interviews to derive the DCDE and DC-ESF empirical models. The DCDE was characterised by: (a) parents serving as dual career (DC) supporters for their respective children at the micro-level; (b) a supportive and flexible head coach promoting DC development for student-athletes; (c) the ISE Committee bridging the study and sports domains at the macro-level; (d) a shared DC philosophy among parents, providing flexible solutions with the help of the head coach, maintaining the equal importance of sport and study, and viewing student-athletes as developing persons for achieving an optimal DC balance; and (e) helping student-athletes develop multiple identities and DC competencies. In conclusion, this study contributes to the understanding of DCDEs within the Chinese cultural context and supplements the DC discourse.